Leaving colorectal polyps in place can be achieved with high accuracy using blue light imaging (BLI) - Neumann, Helmut; Neumann sen, Helmut; Vieth, Michael; Bisschops, Raf; Thieringer, Florian; Rahman, Khan F.; Gamstätter, Thomas; Tontini, Gian Eugenio; Galle, Peter R. (United European Gastroenterology Journal, 2018)
Objectives: A negative predictive value of more than 90% is proposed by the American Society of Gastrointestinal Endoscopy Preservation and Incorporation of Valuable Endoscopic Innovations (PIVI) statement for a new technology in order to leave distal diminutive colorectal polyps in place without resection. To our knowledge, no prior prospective study has yet evaluated the feasibility of the most recently introduced blue light imaging (BLI) system for real-time endoscopic prediction of polyp histology for the specific endpoint of leaving hyperplastic polyps in place. Aims: Prospective assessment of real-time prediction of colorectal polyps by using BLI. Material and methods: In total, 177 consecutive patients undergoing screening or surveillance colonoscopy were included. Colorectal polyps were evaluated in real-time by using high-definition endoscopy and the BLI technology without optical magnification. Before resection, the endoscopist described each polyp according to size, shape and surface characteristics (pit and vascular pattern, colour and depression), and histology was predicted with a level of confidence (high or low). Results: Histology was predicted with high confidence in 92.5% of polyps. Sensitivity of BLI for prediction of adenomatous histology was 92.68%, with a specificity and accuracy of 94.87 and 93.75%, respectively. Following the recommendation of the PIVI statement, positive and negative predictive values were calculated with values of 95 and 92.5%, respectively. Prediction of surveillance based on both US and European guidelines was correctly predicted in 91% of patients. Conclusion: The most recently introduced BLI technology is accurate enough to leave distal colorectal polyps in place without resection. BLI also allowed for assignment of postpolypectomy surveillance intervals. This approach therefore has the potential to reduce costs and risks associated with the redundant removal of diminutive colorectal polyps.
CRIS-Team Scopus Importer:2025-03-05
Keywords: advanced imaging; BLI; endoscopy; LCI; PIVI; polyp